T Cell Impairment Is Predictive for a Severe Clinical Course in NEMO Deficiency - Heller, Stephanie; Kölsch, Uwe; Magg, Thomas; Krüger, Renate; Scheuern, Andrea; Schneider, Holm; Eichinger, Anna; Wahn, Volker; Unterwalder, Nadine; Lorenz, Myriam; Schwarz, Klaus; Meisel, Christian; et al. (Journal of Clinical Immunology, 2020)
Purpose: NEMO-deficient patients present with variable degrees of immunodeficiency. Accordingly, treatment ranges from antibiotic prophylaxis and/or IgG-substitution to allogenic hematopoietic stem cell transplantation (HSCT). The correct estimation of the immunodeficiency is essential to avoid over- as well as under-treatment. We compare the immunological phenotype of a NEMO-deficient patient with a newly-described splice site mutation that causes truncation of the NEMO zinc-finger (ZF) domain and a severe clinical course with the immunological phenotype of three NEMO-deficient patients with missense mutations and milder clinical courses and all previously published patients. Methods: Lymphocyte subsets, proliferation, and intracellular NEMO-expression were assessed by FACS. NF-κB signal transduction was determined by measuring IκBα-degradation and the production of cytokines upon stimulation with TNF-α, IL-1β, and TLR-agonists in immortalized fibroblasts and whole blood, respectively. Results: The patient with truncated ZF-domain of NEMO showed low levels of IgM and IgG, reduced class-switched memory B cells, almost complete skewing towards naïve CD45RA+ T cells, impaired T cell proliferation as well as cytokine production upon stimulation with TNF-α, IL-1β, and TLR-agonists. He suffered from severe infections (sepsis, pneumonia, osteomyelitis) during infancy. In contrast, three patients with missense mutations in IKBKG presented neither skewing of T cells towards naïvety nor impaired T cell proliferation. They are stable on prophylactic IgG-substitution or even off any prophylactic treatment. Conclusion: The loss of the ZF-domain and the impaired T cell proliferation accompanied by almost complete persistence of naïve T cells despite severe infections are suggestive for a profound immunodeficiency. Allogenic HSCT should be considered early for these patients before chronic sequelae occur.
CRIS-Team Scopus Importer:2020-02-04
Keywords: CD45RA; immunological phenotype; NEMO deficiency; Primary immunodeficiency; T cell deficiency